Knowledge and awareness of cervical cancer prevention and HPV vaccination among medical and nursing students in a tertiary care hospital - Thangappah, Radha B. P.; Senthilkumar , Mohana Priya A.; Sureshbabu, Gayathri; Dharmalingam, Poovizhi; Palanisamy, Anitha; Subramanian, Vidhya; Desu, Sri Varshitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was done to assess the level of knowledge and awareness about cervical cancer and its prevention among medical and nursing students. Methods: This descriptive cross-sectional study was conducted during 2022 in a tertiary care hospital in Chennai. The study included 407 subjects; 224 medical students, and 183 nursing students and consent was obtained from each participant prior to the study. A questionnaire survey was used to assess their knowledge on cervical cancer and its prevention. Results: Out of the 407 participants, 95.5% of the medical students and 30.6% of the nursing students knew that HPV virus causes cervical cancer. Medical students had more knowledge on risk factors. 84.38% of medical students and 43.72% of nursing students were aware that vaccine is available for the prevention of cervical cancer. Overall nursing students had limited knowledge on cervical cancer and its prevention. 51.79% of the medical students and 27.87% of the nursing students acquired their knowledge about HPV vaccine through social media. The uptake of HPV vaccine was very low among both medical and nursing students. Conclusions: The results of our study demonstrate that there is a need for creating more awareness about cervical cancer and its prevention among medical and nursing students.